Customer loyalty: antecedents, approaches and influences of culture and religion - Abu Alhaija, Ahmad Saifalddin; Raja Yusof, Raja Nerina; Hashim, Haslinda; Jaharuddin, Nor Siah (World Academy of Islamic Management (WAIM), 2018)
This study sheds light on customer’s loyalty as an important marketing outcome that researchers should examine regularly due to its theoretical and practical implications. The study highlights the approaches and antecedents of customer’s loyalty that should be taken into consideration. In addition, researchers are directed to properly operationalize customer’s loyalty based on the research context and objectives in order to measure loyalty relationships consistently. The present study concludes that integrating cultural and religious influences into existing models would enhance customer’s loyalty. A review of literature shows that researchers have presented several loyalty models based on particular research contexts to provide a better understanding on the concept. It is hoped that the suggestions provided in the paper would inspire future researchers in developing effective loyalty models.